(untitled) (Progress Annals: Journal of Progressive Research, 2025)
This article discusses the development of national values of student youth, the widespread promotion of historical and cultural heritage, the determination of national pride and pride in students, the axiological attitude to ancestral heritage, the support of Student Initiative on the study of ancestral heritage, and the thought of self-assessment in students, selfawareness.